1997
DOI: 10.1080/0735648x.1997.9721586
|View full text |Cite
|
Sign up to set email alerts
|

Juveniles in Adult Prisons: Problems and Prospects

Abstract: The number of juveniles in adult correctional facilities will continue to grow as states turn to the adult criminal justice system as one solution to increasing violent juvenile crime rates. Many questions regarding transfer and its consequences have been and are being researched. One seemingly unexplored area of research focuses on the adult system's response to these young newcomers. This research suggests that correctional administrators have some serious concerns regarding the placement of youth into adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…First, it is possible that more effective treatment services are offered in the juvenile correctional system. Prior quantitative and qualitative research indicates that juveniles in adult prisons and jails generally receive inferior treatment services and are more often exposed to violent victimization as compared to youths in juvenile facilities and that the adult system often is ill prepared to deal with these adolescents (Forst, Fagan, & Vivona, 1989;Howell, 1997;Myers, 2001;Reddington & Sapp, 1997). It should be recognized that in the current study, while controlling for court of jurisdiction, offenders who were incarcerated for longer periods of time exhibited lesser recidivism than did youths who either were not incarcerated or were confined for shorter time periods.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that more effective treatment services are offered in the juvenile correctional system. Prior quantitative and qualitative research indicates that juveniles in adult prisons and jails generally receive inferior treatment services and are more often exposed to violent victimization as compared to youths in juvenile facilities and that the adult system often is ill prepared to deal with these adolescents (Forst, Fagan, & Vivona, 1989;Howell, 1997;Myers, 2001;Reddington & Sapp, 1997). It should be recognized that in the current study, while controlling for court of jurisdiction, offenders who were incarcerated for longer periods of time exhibited lesser recidivism than did youths who either were not incarcerated or were confined for shorter time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has suggested that compared to similar youths in juvenile institutions, adolescents in adult facilities experience greater victimization by both inmates and staff (Forst, Fagan, & Vivona, 1989) and also exhibit higher suicide rates (Flaherty, 1980). Juveniles in adult prisons and jails may also receive inferior treatment services (Forst et al, 1989;Reddington & Sapp, 1997), learn from or be trained by adult inmates, experience the negative consequences of a "criminal" label (Paternoster & Iovanni, 1989), or all three. These events probably go a long way in explaining the consistent findings of greater and more serious recidivism on the part of waived youths.…”
Section: * Discussion and Implicationsmentioning
confidence: 99%
“…Such diminished capacity may also imply that juveniles will not be deterred by harsh sentences (Zane, Welsh, & Mears, 2016), and judges might, therefore, view the especially severe treatment of this population to be counterproductive. Regarding practical constraints and consequences, incarceration alongside adult criminals may be viewed as a non-ideal form of punishment for juveniles due to an absence of suitable detention facilities or the possibility of in-prison victimization (Reddington & Sapp, 1997). Furthermore, while the Juvenile Justice and Delinquency Prevention Act (JJDPA) prevents “sight and sound” contact between incarcerated adults and youth, this provision does not extend to transferred juveniles.…”
Section: Sentencing Transferred Juveniles In the Adult Courtmentioning
confidence: 99%